The ultrastructure of muscle fibers and satellite cells in experimental autoimmune encephalomyelitis after treatment with transcranial magnetic stimulation. (3rd September 2022) - Peña-Toledo, María Angeles; Luque, Evelio; LaTorre, Manuel; Jimena, Ignacio; Leiva-Cepas, Fernando; Ruz-Caracuel, Ignacio; Agüera, Eduardo; Peña-Amaro, J.; Tunez, Isaac
ABSTRACT: In this study, we investigated the effect of transcranial magnetic stimulation (TMS) on the ultrastructure of muscle fibers and satellite cells in rats with experimental autoimmune encephalomyelitis (EAE). EAE-induced animals were treated with TMS (60 Hz at 0.7 mT) for 2 hours in the morning, once a day, 5 days a week, for 3 weeks, starting on day 15 post-immunization. The rats were sacrificed on day 36 post-immunization, and the soleus muscles were evaluated by light microscopy and transmission electron microscopy. Findings were compared with a non-treated EAE group. Electron microscopy analysis showed the presence of degenerated mitochondria, autophagic vacuoles, and altered myofibrils in non-treated EAE group. This correlates with the presence of acid phosphatase activity in muscle fibers and core-targetoid lesions with desmin immunohistochemistry. Most myonuclei in the EAE group showed apoptotic features. In contrast, EAE induced-TMS treated animals had less ultrastructural changes in the mitochondria and the myofibrils, together with less frequent apoptotic nuclear features. Peripheral desmin+ protrusions, as a marker of active satellite cells, were significantly increased in TMS-treated group. This correlates ultrastructurally with the presence of active features in satellite cells in the TMS group. In conclusion, the attenuation of ultrastructural alterations in muscle fibers and activation response of satellite cells caused by EAE indicated that skeletal muscle had a regenerative response to TMS.